Polyphyllin I attenuates cognitive impairments and reduces AD‐like pathology through CIP2A‐PP2A signaling pathway in 3XTg‐AD mice. Issue 12 (18th October 2020) - Zhou, Ying; Yang, Dichen; Chen, Hao; Zheng, Chenfei; Jiang, Huanchang; Liu, Xiaoyuan; Huang, Xingzhou; Ye, Simin; Song, Shuangshuang; Jiang, Nan; Zhao, Zhongyuan; Ma, Shuqing; et al.
Abstract: Polyphyllin I (PPI) is a natural phytochemical drug isolated from plants which can inhibit the proliferation of cancer cells. One of the PPI tumor‐inhibitory effects is through downregulating the expression of Cancerous Inhibitor of PP2A (CIP2A), the latter, is found upregulated in Alzheimer's disease (AD) brains and participates in the development of AD. In this study, we explored the application of PPI in experimental AD treatment in CIP2A‐overexpressed cells and 3XTg‐AD mice. In CIP2A‐overexpressed HEK293 cells or primary neurons, PPI effectively reduced CIP2A level, activated PP2A, and decreased the phosphorylation of tau/APP and the level of Aβ. Furthermore, synaptic protein levels were restored by PPI in primary neurons overexpressing CIP2A. Animal experiments in 3XTg‐AD mice revealed that PPI treatment resulted in decreased CIP2A expression and PP2A re‐activation. With the modification of CIP2A‐PP2A signaling, the hyperphosphorylation of tau/APP and Aβ overproduction were prevented, and the cognitive impairments of 3XTg‐AD mice were rescued. In summary, PPI ameliorated AD‐like pathology and cognitive impairment through modulating CIP2A‐PP2A signaling pathway. It may be a potential drug candidate for the treatment of AD.